Pertumbuhan Lembaga Pendidikan Islam di Kerajaan Langkat Pada Tahun 1912-1942 - Muaz Tanjung (Jurnal Lektur Keagamaan, 2017)
Before the establishment of the Islamic Kingdom of Langkat, the people there have embraced Islam. This is because Langkat is adjacent to Aceh, which had already been ruled by an Islamic empire and it broadcast Islam to various regions, including the east coast of Sumatra. The Kingdom of Langkat, especially after relocated its Capital  to Tanjung Pura, had made Islam as a main reference and political legitimacy of the Sultan and the Kingdom in general. As a consequence, Islam is practiced by the majority of Muslim community and reflected in various fields. At the beginning of the 20th century in East Sumatra there emerged publicly funded educational institutions, including those in Langkat. However, religious subjects are not officially acknowledged. Seeing this situation, the Sultan and other Muslims felt responsible for establishing an independent Islamic educational institution. Although Islamic education was preiously taught to Muslim children, but its implementation was largely limited in mosques or private homes. The Kingdom was destined to improve the quality of Islamic education through building an independent educational institution.Keywords: Education, Islamic Empire, Langkat, Sumatera, Indonesia Sebelum berdirinya kerajaan Langkat, masyarakat di sana telah memeluk agama Islam. Hal ini dikarenakan wilayah Langkat berbatasan dengan Aceh yang telah memiliki kerajaan Islam dan menyiarkan Islam ke berbagai daerah, terutama di pantai timur Sumatera. Kerajaan Langkat terutama setelah berpusat di Tanjung Pura, menjadikan agama Islam sebagai pedoman dan legitimasi terhadap kebijakan-kebijakan sultan dan kerajaan secara umum. Masyarakat yang mayoritas beragama Islam dalam berbagai dinamika kehidupannya mencerminkan perilaku keislaman yang kuat. Di awal abad ke-20 M di Sumatera Timur banyak berdiri lembaga pendidikan umum, termasuk di Langkat. Namun demikian, pelajaran agama secara resmi tidak dibenarkan. Melihat keadaan ini, sultan dan umat Islam lainnya merasa bertanggungjawab untuk mendirikan lembaga pendidikan Islam yang berdiri sendiri. Meskipun pada masa sebelumnya pendidikan Islam tetap diajarkan kepada anak-anak Muslim, namun pelaksanaannya masih berlangsung terbatas hanya di masjid atau rumah-rumah pribadi guru. Oleh karena itu Kerajaan Langkat terdorong untuk meningkatkan mutu pendidikan Islam dengan membangun lembaga pendidikan yang berdiri sendiri.Kata kunci: Pendidikan, Kerajaan Islam, Langkat, Sumatera, Indonesia